2016
DOI: 10.4314/ejhs.v26i2.8
|View full text |Cite
|
Sign up to set email alerts
|

Paediatric Refractive Errors in an Eye Clinic in Osogbo, Nigeria

Abstract: BACKGROUND: Paediatric ophthalmology is an emerging subspecialty in Nigeria and as such there is paucity of data on refractive errors in the country. This study set out to determine the pattern of refractive errors in children attending an eye clinic in South West Nigeria. METHODS: A descriptive study of 180 consecutive subjects seen over a 2-year period. Presenting complaints, presenting visual acuity (PVA), age and sex were recorded. Clinical examination of the anterior and posterior segments of the eyes, ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 18 publications
2
8
1
Order By: Relevance
“…As expected, myopia, which starts in childhood and progresses with age [28], was predominantly diagnosed in this younger age group (56.6% below the age of 30), whereas hyperopia was symptomatic at all ages, with its peak at age 50 and older. Similar to our study with 34.9% of refractive errors at young ages, a study investigating children in Osogbo, Nigeria by Isawumi et al [24] analysed a very similar number of refractive errors with 27.8% in children aged 3-16.…”
Section: Discussionsupporting
confidence: 90%
“…As expected, myopia, which starts in childhood and progresses with age [28], was predominantly diagnosed in this younger age group (56.6% below the age of 30), whereas hyperopia was symptomatic at all ages, with its peak at age 50 and older. Similar to our study with 34.9% of refractive errors at young ages, a study investigating children in Osogbo, Nigeria by Isawumi et al [24] analysed a very similar number of refractive errors with 27.8% in children aged 3-16.…”
Section: Discussionsupporting
confidence: 90%
“…The number of female patients with refractive error is more than males across different studies. [ 8 22 23 24 26 ] In our study also, similar trend is found ( P = 0.000). The percentage of female patients in our study is more than other studies probably because our institute is situated in a place with matrilineal society.…”
Section: Discussionsupporting
confidence: 89%
“…There are some hospital-based studies on the proportion of refractive errors available from some other countries. [ 22 23 24 25 26 ]…”
Section: Discussionmentioning
confidence: 99%
“…19 This paper presents a scoping review 20 to gain knowledge about school vision screening amongst preschoolers and schoolchildren in Kenya and Nigeria and their vision problems. 21,22 The authors searched for a model to learn from in relation to care for visual health amongst young people.…”
Section: Introductionmentioning
confidence: 99%